The Effects of Modified Constraint-Induced Movement Therapy in Acute Subcortical Cerebral Infarction - Yu, Changshen; Wang, Wanjun; Zhang, Yue; Wang, Yizhao; Hou, Weijia; Liu, Shoufeng; Gao, Chunlin; Wang, Chen; Mo, Lidong; Wu, Jialing (Frontiers in Human Neuroscience, 2017)
Background: Constraint-induced movement therapy promotes upper extremity recovery post stroke, however, it is difficult to implement clinically due to its high resource demand and safety of the restraint. Therefore, we propose that Modified Constraint-Induced Movement Therapy be used to treat individuals with acute subcortical infarction. Objective: To evaluate the therapeutic effects of Modified Constraint-Induced Movement Therapy in patients with acute subcortical infarction, and investigate the possible mechanisms underlying the effect. Methods: The role of Modified Constraint-Induced Movement Therapy was investigated in 26 individuals experiencing subcortical infarction in the preceding 14 days. Patients were randomly assigned to either Modified Constraint-Induced Movement Therapy or standard therapy. Modified Constraint-Induced Movement Therapy group was treated daily for 3 h over 10 consecutive working days, using a mitt on the unaffected arm for up to 30% of waking hours. The control group was treated with an equal dose of occupational therapy and physical therapy. During the 3-month follow-up, the motor functions of the affected limb were assessed by the Wolf Motor Function test and Motor Activity Log . Altered cortical excitability was assessed via transcranial magnetic stimulation . Results: Treatment significantly improved the movement in the Modified Constraint-Induced Movement Therapy group compared with the control group. The mean Wolf Motor Function score was significantly higher in the Modified Constraint-Induced Movement Therapy group compared with the control group. Further, the appearance of motor-evoked potentials were significantly higher in the Modified Constraint-Induced Movement Therapy group compared with the baseline data. A significant change in ipsilesional silent period occurred in the Modified Constraint-Induced Movement Therapy group compared with the control group. However, we found no difference between two groups in motor function or electrophysiological parameters after 3 months of follow-up. Conclusions: Modified Constraint-Induced Movement Therapy resulted in significant functional changes in timed movement immediately following treatment in patients with acute subcortical infarction. Further, early Modified Constraint-Induced Movement Therapy improved ipsilesional cortical excitability. However , no long-term effects were seen.